Massive haemoptysis following dabigatran administration in a patient with bronchiectasis. (19th February 2014) - Hayama, Manabu; Inoue, Hideki; Wada, Hiromichi; Mio, Tadashi
Abstract : We report a case of life-threatening haemoptysis after administration of dabigatran in a patient with bronchiectasis. A 72-year-old woman had received dabigatran at a dose of 110 mg twice daily for chronic atrial fibrillation. She was admitted to our hospital for cerebral infarction after a few days of self-interruption of dabigatran. After the diagnosis of cerebral infarction, administration of dabigatran was restarted. Seven days later, she suffered acute-onset massive haemoptysis and required mechanical ventilation. Dabigatran treatment was discontinued, and bronchial artery embolisation (BAE) was performed twice. The bleeding continued for 11 days, but she recovered and was discharged on day 58 after admission.